Efektifitas Ekstrak Etanol Kulit Sawo Manila (Achras Zapota) Terhadap Daya Hambat Pertumbuhan Streptococcus Mutans (Kajian In Vitro) - Zuhada, Awang; , drg. Edi Karyadi, MM; , drg. SE Yuletnawati, MDSe (2016)
Mouthwash with basic materials made from natural medicinal plants have been developed in many countries because it has antibacterial properties with minimal side effects, the use of drugs made from natural plants for traditional medicine is mostly done as a substitute for primary treatment alterntif. The goal is to clean the plaque on the tooth surface. Plaque is the main cause of dental caries formation. Streptococcus mutans is a bacterium often found in cavities. Ethanol extract of sapodilla manila (Achras zapota) is one of the ingredients are natural which has antibacterial because it has active substances such as flavonoids, tannins, saponins.This study aims to determine the effectiveness of the ethanol extract of sapodilla manila (Achras zapota) the inhibition of the growth of Streptococcus mutans. This research is a laboratory experimental pure.Research pitting pure diffusion method which consists of 4 groups is the ethanol extract of manila sapodilla with a concentration of 30%, 40%, 50%, 60% and 0.2% chlorhexidine (positive control). Each treatment group is replicated 5 times then inhibition zone was measured using a caliper to millimeters (mm).Results of research manila sapodilla ethanol extract at a concentration of 30%, 40%, 50% and 60% showed inhibition zone. it can be concluded that between the concentration of 30%, 40%, 50%, 60% the biggest obstacle is the concentration of 60%.